(untitled) (EAAE Annual Conference Proceedings, 2019)
Complexity of the 20th century society, along with strong professions’ specialization, led to separation between all participants in the developing processes, especially in public spaces design. Lack of cohesion and consensus along with poor communication between professions, citizens, government and business sector, resulted in new participative and interdisciplinary trends emerging in the 21st century to bring sectors back together. Students’ education must follow these trends, as their orientation in shaping the desirable futures. Elective course ‘Participatory design of space’ (POP) is planned as a faculty-based fieldwork workshop that gives students the opportunity to become acquainted with participatory methods in space design. In this way, the user’s opinion is included in the cognitive fund when drafting the conceptual solution of a small-scale task in the public space or in any area of interaction. Students learn to identify and critically evaluate participatory content, to generate the conceptual level of planning — intent, to discuss it with users, to translate it directly and recognizably into a viable solution, to present it successfully, and to participate in the realization.